Global Economic Meltdown and the Performance of Insurance Industry: Implication for Career Opportunities - Epetimehin, Festus M. (Mediterranean Journal of Social Sciences, 2011)
The economic and financial crisis, which started in the United States in September 2008, has rattled markets and economiesdeveloped, developing and underdeveloped around the globe, and because the world is linked inextricably by globalization the crisis hascontinued to dominate discussions on global economy. Many countries are experiencing severe closure of companies, loss of jobs, crash ofshare prices, squeeze in consumer credit facilities, crumbling mortgage facilities among others. In the case of the developing countries ofwhich Nigeria is one, the implications are noticeable in the areas of crash in share prices, dwindling revenues, few direct investments fromdeveloped countries, dwindling remittances from Nigerians abroad and possible erosion of foreign resources among others. This papertherefore provides a clarification of the term Global Economic Meltdown, the causes and the performance of the insurance Industry underthis situation and the implication for career opportunities.